Fabrication of AlZn4SiPb/Steel Clad Sheets by Roll Bonding: Their Microstructure and Mechanical Properties - Pengju Wang; Ning Zhong; Liyue Tu; Weiming Hong; Yanming Lv; Yonghong Chen; Jian Sun; Caiyong Luo; Zejun Chen; Qian Tang (Crystals, 2023)
An AlZn4SiPb/steel clad composite was prepared via roll bonding at room temperature. The influence of solution and aging treatment on the structure and performance of the clad composite was investigated. The results show that the Al/steel clad composites exhibited satisfactory interfacial adhesion. Pb of the aged Al matrix was spheroidized and uniformly dispersed. An uneven interfacial transition area with a thickness of 30–150 nm was observed for the aged sample. Some rod-shaped nanoscale β’ phases occurred in the aged Al matrix. After the solution and aging treatment, the steel layer recovered, and the γ-fibre texture increased. The tensile strength for individual Al alloy layer improved. The yield ratio of the aged clad sheet was lower than that of the initial sample. The tensile strength values of the composites were consistent with the computed values from the rule of mixture. The interfacial bonding strength of the initial sample was 70 MPa; the aged sample greatly improved and reached 130 MPa in strength.